Helicobacter pylori eradication for preventing gastric cancer - Lu, Bin (Baishideng Publishing Group Inc, 2014)
Helicobacter pylori (H. pylori) infection is a major risk factor for gastric cancer (GC) development, which is one of the most challenging malignant diseases worldwide with limited treatments. In the multistep pathogenesis of GC, H. pylori infection slowly induces chronic active gastritis, which progresses through the premalignant stages of atrophic gastritis, intestinal metaplasia, and dysplasia, and then finally to GC. Although eradication of H. pylori is a reasonable approach for the prevention of GC, there have been some contradictory reports, with only some long-term follow-up data showing efficacy of this approach. The inconsistencies are likely due to the insufficient number of participants, relatively short follow-up periods, poor quality of study designs, and the degree and extent of preneoplastic changes at the time of H. pylori eradication. This review analyzes recent high-quality studies to resolve the discrepancies regarding the eradication of H. pylori for GC prevention. The relationship between H. pylori eradication and GC/precancerous lesions/metachronous GC is examined, and the cost-effectiveness of this strategy in the prevention of GC is assessed. Although it is assumed that eradication of H. pylori has the potential to prevent GC, the feasibility and appropriate timing of this strategy for cancer prevention remain to be determined. As a result, additional well-designed trials with longer follow-up periods are needed to clarify this issue.